The Challenges of Podcasting Platformization. Exploratory analysis on Podcast audiences and the transition to new competitive structures - Paisana, M.; Crespo, M.; Quintanilha, Tiago Lima (IWEMB 2020 - 4th International Workshop on Entrepreneurship, Electronic and Mobile Business, 2020)
This paper aims to reflect upon the origins of Podcasting and to place the format’s contemporary relevance within wider market shifts towards platformed business models. Platforms have been rapidly evolving, absorbing previously untouched spheres such as the news or entertainment industry. Being data-oriented structures, we materialize in this contribution the underlying threat platformization may pose to genetically open ecosystems such as the podcasting sphere, exploring the cultural, technological and managerial implications. Presented reflections were supported with global data on podcast usage from the 2019 and 2020 editions of the Reuters Digital News Report from the Reuters Institute for the Study of Journalism. Analyzed data corroborates the massification/normalization of podcasting, both in the whole sample and younger audiences, with podcast listeners having an overall positive view of the format when compared to other media. While underlining the specific changes platformization may cause to Podcasting, we suggest that much can be learned from the experiences of other media spheres. The disruption caused by infrastructural changes to content ecosystems cannot be avoided but may be predicted through efficient managerial decisions and the safeguard of both established brands in the market as well as smaller, innovation driven, and independent producers who were and still are vital to the wealth of the Podcasting ecosystem.